Cloud services in supply chains - Zuzarte, Filipe e Miguel Proença (2019)
In recent years, companies, regardless of the economic sector in which they operate, have been adapting to the emergence of new technologies and have integrated them into their processes, both internal and external. This adoption results from the fact that new technological breakthroughs allow significant increases in efficiency and reductions in operating costs, thus reaching better profits. This paper explores the importance that cloud services have had in changing supply chain paradigms, the advantages and disadvantages of their integration as well as concrete examples of how this is already done in different industries. The technology itself is also fully explained, without going into the underlying technical complexity.